Socio-emotional factors related to the academic difficulties of “star” children of the psychomotricity and intervention program - Herrera González, Emmanuel (2012)
This study shows the main socio- affective factors related to school difficulties of a group of three girls and three boys identified as "star" in the Programa Psicomotricidad e Intervención (Psychomotor and Intervention Program). The study was developed through a mixed methodology, in which the Human Figure Test, the Kinetic Family Drawing and an interview with the mother of each student were applied. The most important results revealed the existence of family conflicting factors that affect the emotional state of children, generating negative feelings about themselves that affect their social interactions and their school performance.